Unsuccessful Suicide Attempt With Tiapride. Issue 6 (December 2017) - Couderc, Sylvain; Mourou, Hervé; Monchaud, Caroline; Saint-Marcoux, Franck
Abstract : Abstract: To the best of our knowledge, no case has been published in the literature that reports an overdose of tiapride, either alone or in combination with other drugs. We report a self-poisoning case in an 18-year-old girl, with approximately 10 times the usual daily dose (ie, 2.5 g). Although the blood concentration was 20/30-fold higher than usually observed after therapeutic drug intakes (17, 300 mcg/L), the patient remained almost asymptomatic.